10 - Microtechnology and Nanotechnology Advancements Toward Bio-Molecular Targeting - Perumal, Veeradasan (Elsevier, 2019)
This chapter begins with a brief explanation and comparison of the ZnO thin film deposition and growth technique via chemical and gas phase routes for the novel fabrication of biosensor applications. Next, the role of the gold nanoparticle and its unique properties in biosensing applications are discussed. In addition, the ability of gold nanoparticles to combine with other materials to form a hybrid for biosensing for designing nanosensors is presented. The interdigitated electrode with twin electrodes that are arranged in a comb-like structure to form gaps between the two electrodes is reviewed for use as a transducer. In addition, types of electrochemical transduction methods for ZnO nanobiosensor transduction are presented. This method consists of four main groups, which are amperometric, potentiometric, conductometric, and electrochemical impedance spectroscopy (EIS) transduction. Moreover, a detailed review is provided on important elementsâ presence in EIS, such as equivalent circuit analysis, the Bode plot, and the Nyquist plot. Finally, deoxyribonucleic acid (DNA) sensors for biosensing applications are studied in this chapter.